Oil Field Development Scenario to Increase Oil Recovery Using Reservoir Simulation - Julianto, Cahyadi; Priambodo, Aldi; Tulloh, Hidayat; Nugroho, Muhammad Rizky (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Field “X” is an oil field located in the South Sumatra Basin. The field is located in an onshore area with reservoirs dominated by sandstone. Based on existing data, the average porosity of each layer is 18.9% and the average water saturation is 50.3%. The oil reserve calculate using volumetric method, from these calculation known the value original oil place (OOIP) is 23.454 MMSTB. Then, the calculation of recovery factor is done by using the JJ Arps. Methods. Based on this method, the RF value of each productive layer is known to be, A1 layer of 37.64733%, A2 RF layer at 38.01293% and A3 layer by 41.3509%. From these JJ. Arps, it can be estimated the productivity of reservoir from the initial oil reserve (OOIP condition). Field X first produced in 2016 and the field has a 30-year contract duration until 2047. In this field, the optimization of oil production is done by field development scenario of 5 step scenarios using the CMG Reservoir Simulation. The scenario consists of basecase by adding the infill wells, pressure maintenance, and waterflooding injection on the field X. From the simulation, it can be obtained the cumulative production, and recovery factor from each scenarios. On basic scenario or basecase condition or scenario 1 has an RF value of 6.039% and cumulative production is 1416500 MSTB, scenario 2 has an RF value of 12.29% and cumulative production is 2883000 MSTB, Scenario 3 has an RF value of 15.566% and cumulative production is 3650900 MSTB, scenario 4 has an RF value of 20.669% and cumulative production is 4847700 MSTB, and scenario 5 has an RF value of 21.435% and cumulative production is 5027400 MSTB. From the result of each scenarios, the scenario 5 is the best development scenario for the field “X”.